A bibliometric analysis of the global research on sofosbuvir - Hernández-Vásquez, Akram (2017)
ABSTRACT In this article, we examine the research on sofosbuvir with a bibliometric analysis of global research production. The study of sofosbuvir has been a field of intense research in the past few years, with Latin American contributions playing a modest role. With continued drug development and approval of hepatitis C antivirals, research is expected to increase. Our findings will assist scholars and policy makers in their efforts to improve scientific research policies, with the goal of maximizing the access to treatments, especially in low and middle-income countries.